The Use of Written Corrective Feedback in SMKN 6 Jakarta Students’ English Writings - Cherie Gabriella Constantia; Theresia Arianti (English Department - University of Sultan Ageng Tirtayasa, 2022)
Students who live in a non-English-speaking country or EFL students often face difficulties in mastering English writing. The teachers need to fix it by giving written corrective feedback which would let the students know the linguistic errors they make in written production and improve from their errors. The aims of this research study are to find out what kind of error that EFL students usually make in English writing, the most common type(s) of WCF that teachers use, and the reason why teachers mostly use one type of WCF. This study was carried out by using Descriptive Analysis Qualitative Method since the results of this study were explained descriptively. The participants that were involved in this study are 20 students of tenth graders and 2 English teachers of SMKN 6 Jakarta. The instruments that were used in this study are Table Analysis (RQ1 & RQ2) and Interview (RQ3). In the end of the study, the results showed that Grammatical Error gained the highest number of errors found in the students’ assignments. The study also found that the English teachers frequently use Direct Correction to correct the students because it is easy, useful, and fast to use. It is suggested for the English teachers correct errors based on their contexts in the assignments and future researchers should also conduct cases about WCF which emphasizes the difference of writing errors that are produced by male and female students.